diversity of myiasis fly, Chrysomya bezziana population in Indonesia based on mitochondrial DNA - Wardhana, April H; Muharsini, S; Asmara, Widya (Indonesian Animal Sciences Society, 2004)
Chrysomya bezziana is a fly causing myiasis in most livestock in Indonesia. To date, the genetic diversity of C. bezziana has been argued among researchers. The aim of this study was to analyse genetic diversity of C. bezziana population in Indonesia using mitochondrial cytochrome b gene (cyt b) as a marker. The preliminary study showed that the larvae instar III stadium (L3) was the most appropriate sample for molecular analysis and identification. Twenty-four L3 were collected from cattles, buffalos and horses in Bogor, Makassar and East Sumba. DNA samples were isolated from muscle tissue of the larvae. The fragment of cyt b gene (279 bp) was amplified using primer CB3FC-NINFA. The PCR product was subsequently purified, sequenced and analysed using PAUP version 4. The results showed that C. bezziana from Indonesia was different with those from Asia, basicaly for DNA sequences, however it had similar to those from Papua New Guinea. Two haplotypes were identified i.e. haplotype 6 (Makassar haplotype that similar to those from Papua New Guinea) and haplotype 7 (Bogor haplotype that similar to those from Makassar and East Sumba). Key words: Chrysomya bezziana, genetic diversity, mitochondrial DNA